Criteria of diagnosing cardiomyopathies of different genesis in sport horses - I. Maksymovych; L. Slivinska; V. Vlizlo; A. Shcherbatyi; B. Gutyj; M. Leno; B. Chernushkin; V. Rusyn; V. Fedorovych; O. Prystupa (Regulatory Mechanisms in Biosystems, 2025)
Sport horses suffering physical overexertion syndrome, anemic syndrome, and electrolyte imbalance may experience development of cardiomyopathy with various pathogenetic mechanisms. The objectives of our study were to determine the causes of pathogenesis, substantiate its individual links, and elaborate the methods of diagnosing cardiomyopathies of different genesis in sport horses (anemic syndrome, physical overexertion syndrome, electrolyte imbalance). The horses suffering cardiomyopathy were observed to have increased frequency of heart murmurs, arrhythmias, and valvular regurgitation. In the underperforming horses with metabolic disorders, the anemic syndrome manifested in a stable number of erythrocytes, content of hemoglobin, and hematocrit, whereas in the high-performing animals these parameters were significantly increased. Increase in the concentration of total bilirubin and iron in blood of the horses with anemic syndrome indicated anemia of hemolythic origin. In athletic horses, excessive physical exertion results in the development of the syndrome that manifests in dehydration (increase in the content of total protein), cholestasis (increase in the concentration of total bilirubin; tendency toward increase in the activities of alkaline phosphatese and gamma-glutamyl transpeptidase), cytolysis (increases in the activities of aspartate aminotransferase, total creatine kinase, cardiac isoenzyme of creatine kinase, lactate dehydrogenase, lactate dehydrogenase-1), and uremic syndrome (increase in the urea concentration and creatinine). A specific marker of cardiomyopathy in equine athletes was found to be heightened activity of cardiac isoenzyme of creatine kinase and concentration of lactate in blood. In horses subject to excessive exertion, cardiomyopathy develops as a result of electrolyte imbalance due to the loss of electrolytes with sweat (decline of sodium and potassium concentrations in blood serum). This is evidenced by dehydration (increase in the content of the total protein and hematocrit). Based on the conducted studies, we have elaborated the methods of diagnosing cardiomyopathies of different gen e sis in sport horses.